2011
DOI: 10.1021/jp200973q
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of the Reaction of Thin Films of Solid-State Benzene with Vapor-Deposited Ag, Mg, and Al

Abstract: Thin films of solid-state benzene at 30 K were reacted with small quantities of vapor-deposited Ag, Mg, and Al under ultrahigh vacuum, and products were monitored using surface Raman spectroscopy. Although Ag and Mg produce small amounts of metalÀbenzene adduct products, the resulting Raman spectra are dominated by surface enhancement of the normal benzene modes from metallic nanoparticles suggesting rapid Ag or Mg metallization of the film. In contrast, large quantities of Al adduct products are observed. Vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 100 publications
(193 reference statements)
4
25
0
Order By: Relevance
“…The reference CS showed three sharp peaks at 490, 1471 and 1534 cm À1 which were attributed to the vibration of C-H or C-C bonds in the carbonaceous product. 29,30 The above peaks were in accordance with the corresponding position observed in the Al@carbon curve. The new broad band in Fig.…”
Section: Removal Of Carbon Templatessupporting
confidence: 85%
“…The reference CS showed three sharp peaks at 490, 1471 and 1534 cm À1 which were attributed to the vibration of C-H or C-C bonds in the carbonaceous product. 29,30 The above peaks were in accordance with the corresponding position observed in the Al@carbon curve. The new broad band in Fig.…”
Section: Removal Of Carbon Templatessupporting
confidence: 85%
“…As with conventional Raman, SERS has been used to probe polymer films in a device structure to gain information on the polymer structure in multilayer devices, 18 the effects of device degradation, 19 the differences in preparation conditions for poly(3,4-ethylenedioxythiophene) (PEDOT), a common hole-injecting material, 20 and the effects of metallic electrodes on benzene molecules. 21 Here, we report the use of model electrodes fabricated from gold or silver as SERS substrates to characterize the polymer-metal interface, further illustrating the potential for SERS to be used as an in situ tool for probing an operating device. Using poly[2-methoxy-5-(2-ethylhexyl-oxy)-1,4-phenylene-vinylene] (MEH-PPV) as a model polymer film, we find that gold electrodes induce a conformational change at the metal interface as is evident in an additional band in the SERS spectrum that is not present in the Raman spectrum of the bulk film.…”
mentioning
confidence: 85%
“…22 Combined with photoluminescence and absorption spectroscopy, they attributed the change to increased planarization of the MEH-PPV chains. 22 A more complex scenario was recently observed by Schalnat et al 21 Using the SERS spectra of benzene molecules, an aluminum interface was shown to reduce the molecular symmetry of the benzene and amplify the 860 cm À1 vibrational mode. This is seemingly contradictory with the results from Liu et al 22 but is actually consistent, since FTIR and Raman spectroscopy typically observe mutually exclusive vibrational modes: increased intensity of a mode observed in an FTIR measurement will generally correspond to decreased intensity in a Raman measurement.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…SERS lending would open an avenue for new analytical applications of SERS. Well-known and recent results from surface chemistry [44][45][46][47][48] may serve as an inspiration for designing new mixed-metal SERS substrates. In particular, transition metals of the nickel group are known to form strong coordinative bonds with nitrogen-containing molecules and are promising candidates for their detection with SERS.…”
Section: Introductionmentioning
confidence: 99%